Spotlight on Cloud Cloud FinOps & Cost Optimization with J.R. Storment - Storment, J. R. (O'Reilly Media, Inc., 2020)
Ten years ago, DevOps broke down the silos between engineering and ops and accelerated the pace of innovation. Today, a similar pattern is emerging where effective cloud infrastructure adoption and usage requires a deep collaboration between technical teams (DevOps) and their new partners in finance and business. In this Spotlight on Cloud, find out how to create a strategy for managing your organization's cloud costs. Expert J.R. Storment shares strategies for scaling your cloud adoption by collaborating across operations, development, and finance to continuously optimize cloud spend, using an emerging practice known as FinOps. Recorded on December 16, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Cloud, you'll learn about the complex, ever-evolving world of the cloud. You'll discover how successful companies have adopted and embraced this massive network of shared information and how you can follow their lead to transform your organization and prepare for the Next Economy.